Introduction to the Special Issue "Parental work and family/child well-being"; Einführung in das Sonderheft ,,Elterliche Arbeit und Familien-/Kinderwohlbefinden“ - Matthias Pollmann-Schult; Jianghong Li (JFR – Journal of Family Research, 2020)
The "new economy" is characterized by increasing levels of nonstandard employment. A significant proportion of employees work very long hours, work with high intensity, or have long commutes to work. Also, many workers struggle to secure adequate, stable employment or good quality jobs, and work evening and night shifts or work multiple jobs in order to make ends meet. This special issue examines the consequences of the new economy for the wellbeing of family and children. The studies included in this special issue address the impact of parents' nonstandard work schedules (shift work), long work hours, temporary employment, and long commutes to work on parental and child health and wellbeing, relationship satisfaction, work-family balance, and the division of labour. – – Die “New Economy” zeichnet sich durch einen Anstieg an atypischer Beschäftigung aus. Ein hoher Anteil der Erwerbstätigen verzeichnet lange Arbeitszeiten, eine hohe Arbeitsintensität oder eine lange Pendeldauer. Ein beträchtlicher Anteil der Erwerbstätigkeit leistet Schicht- bzw. Wochenendarbeit oder geht mehreren Beschäftigungen nach. Dieses Sonderheft betrachtet die Konsequenzen solcher Arbeits- und Beschäftigungsverhältnisse für das Wohlergeben von Familien und Kindern. Die in diesem Sonderheft veröffentlichten Beiträge untersuchen den Einfluss von atypischen Arbeitszeiten (Schichtarbeit), langen Arbeitszeiten, befristeter Beschäftigung sowie langen Pendeldauern auf die Gesundheit und das Wohlergehen von Kindern und Eltern, die Partnerschaftszufriedenheit, Vereinbarkeitsprobleme und die Aufteilung der Hausarbeit.
Keywords: 330; shift work; working hours; commuting; parental well-being; child-wellbeing; Schichtarbeit; Arbeitszeit; Pendeln; kindliches Wohlbefinden; elterliches Wohlbefinden